XQuery : search across a variety of XML data - Walmsley, Priscilla (O'Reilly Media, 2015)
Designed for query writers who have some knowledge of XML basics, but not necessarily advanced knowledge of XML-related technologies, this book is ideal as both a tutorial and a reference. You?ll find background information for namespaces, schemas, built-in types, and regular expressions that are relevant to writing XML queries.